Biogenic gold nanoparticles against wild and resistant type visceral leishmaniasis. (2018) - Das, Suvadra; Halder, Asim; Roy, Partha; Mukherjee, Arup
Abstract: Leishmaniasis is a WHO notified neglected tropical disease and the lethal visceral leishmaniasis variant is endemic in Indian subcontinent. Gold nanoparticles (Aunp) have emerged as veritable tools in drug delivery because of their higher residence time in systemic circulation compared to other nanocarriers. Polyphenolic compound Gallic acid is used for bio-rated synthesis and in situ functionalization for GAunp. Synthesized nanoparticle exhibited surface plasmon response at 530nm and ζ potential of -8.53 mV. The average size of particles in TEM was 12.05 nm. XRD and SAED definite fcc crystalline structure of metallic gold particles and FTIR confirmed gallic acid bioconjugation. Antileishmanial efficiency of GAunp was established against wild type (IC50 4±1), sodium stibogluconate resistant strain(IC50 4.5±2). Macrophage uptake of GAunp was complete within one hour as studied in TEM experiments.